2019
DOI: 10.3390/ijerph17010256
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Microbiome and Cigarette Smoking: A First of Its Kind Investigation in Jordan

Abstract: There is accumulating evidence in the biomedical literature suggesting the role of smoking in increasing the risk of oral diseases including some oral cancers. Smoking alters microbial attributes of the oral cavity by decreasing the commensal microbial population and increasing the pathogenic microbes. This study aims to investigate the shift in the salivary microbiota between smokers and non-smokers in Jordan. Our methods relied on high-throughput next-generation sequencing (NGS) experiments for V3-V4 hyperva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…In 2019, Al-Zyoud et al [ 34 ] included in their study 100 healthy subjects (57 males and 43 females), with 51 non-smokers and 49 smokers. The smokers used to smoke at least one cigarette per day.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Al-Zyoud et al [ 34 ] included in their study 100 healthy subjects (57 males and 43 females), with 51 non-smokers and 49 smokers. The smokers used to smoke at least one cigarette per day.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, shifts in salivary microbiota were evaluated comparatively in smokers and nonsmokers in Jordan. 37 High- Although there were differences among individuals, smokers with periodontitis revealed a robust core microbiome consisting of species identified in at least 80% of individuals, in which anaerobic bacteria dominated. 40 Smokers exhibited sparse co-occurrence of microbial networks that were predominantly congeneric.…”
Section: The Effects Of Smoking On Colonization Dynamics and Resiliencementioning
confidence: 99%
“…In a recent study, shifts in salivary microbiota were evaluated comparatively in smokers and nonsmokers in Jordan 37 . High‐throughput next‐generation sequencing for V3‐V4 hypervariable regions of the 16S ribosomal RNA gene was used and Streptococcus , Prevotella , Veillonella , Rothia , Neisseria , and Haemophilus were investigated.…”
Section: Tobacco Products and Periodontal Microbiomementioning
confidence: 99%
“…Researchers provided evidence that tobacco smoking has a direct effect on the oral microbiota. They also suggested that after smoking cessation, it is possible to return to the standard composition of the oral cavity microbiota [115].…”
Section: Chemical Compound Bacteriamentioning
confidence: 99%